ANALISIS TINGKAT KEMANDIRIAN, EFEKTIVITAS DAN KEMAMPUAN KEUANGAN DAERAH KABUPATEN MIMIKA - Sastra Widiyanti Said; Abu Bakar (Delilah Tinggi Ilmu Ekonomi Jambatan Bulan, 2021)
This study aims to determine the level of regional financial independence of Mimika Regency. The method used in this research is descriptive method. Data collection techniques used are documentation, and literature study. The data analysis technique used in this research is the analysis of the ratio of regional independence, effectiveness and financial capability. The results of this study indicate that: The average value of the financial independence ratio is categorized as less independent, the level of effectiveness is quite effective and financial ability is classified as very good in Mimika Regency in the 2013-2017 fiscal year.